A video game to travel inside the rocks of a basin. Virtual reality is coming to the classroom (LACCEI, 2024)
The use of an Immersive Virtual Reality glasses and joysticks in the classroom seems unthinkable, however, we designed a classroom work with these elements for Petroleum Engineering and Geodesy-Geophysics Engineering, courses. Rv software allows the student to become familiar with different models of reservoirs, whether they are hydro, geothermal, oil, etc. making dives and visualizations inside reservoirs using Rv glasses and two joysticks as navigation tools. This classroom work was designed to reinforce the conceptual and attitudinal contents of the Reservoirs theme where the application is used in the approach and deepening of the fluid media. Students explore the environment using these tools, sectioning sedimentary strata, measuring thickness, indicating physical attributions of permeability, porosity, density, susceptibility of certain rock formations, etc. based on the guidelines proposed by the teacher in the Guidance Guide. The teacher observes the dives through a Tablet and guides the student through the different stages of navigation. Once the topic has been studied in depth, students are able to compare the results obtained by various groups of students who have analyzed different aspects of the reservoir, collectively draw up a report that relates the guidelines to the information and present graphs and tables with data on the physical magnitudes observed. Student reports are evaluated through rubrics. The software design was fully developed at FIUBA and the elements were acquired thanks to a Research and Development project (PIDAE).